Simultaneous Equation Model for Economic Calculation of Households of Independent Rubber Farmers in Mineral Land in Kampar Regency, Riau Province, Indonesia - Heriyanto Heriyanto; Asrol (UIR PRESS, 2020)
Rubber is a plantation crop which is mostly a source of community income in Kampar District. As a source of household income, rubber farming is managed by households independently. This study generally aims to design models and government policy strategies in the development of smallholder rubber plantations on land typology mineral land conditions on the economic decision making of rubber farmer households. Specifically, this study was conducted with the aim of analyzing the characteristics of independent smallholders and internal and external dominant factors that influence the allocation of working time, income and household expenses of rubber farmers. This research was conducted using a survey method located in Kampar District. The data used in this study consisted of primary data obtained using the interview method. Samples were taken by simple random sampling method with 60 rubber farmers. Descriptive analysis and Economic Decision Model of Rubber Farmer Households using the simultaneous equation model approach with the Two Stages Least Square (2SLS) analysis method were performed to answer the research objectives. The results showed that only internal factors of farm households are responsive to household economic decisions. There are no external factors included in the model that are responsive to the economic decisions of rubber farming households in Kuantan Singingi Regency regarding the aspects of production, working time allocation, income and expenditure of rubber farming households. From the aspect of production, no responsive internal or external factors were found, but the biggest effect was the number of productive rubber stems. From the aspect of work time allocation, internal factors that are responsive to influence are the total outpouring of farmer work, outpouring of farm family work in businesses and the workforce of farmer households. Furthermore, from the aspect of farmer's household income the responsive internal factors that influence it are the farmer's household income in the business. then what influences household expenditure is outflow of work in business, farmer education, wife education and total rubber farmer income. The policy implications of increasing rubber prices and outpouring of family work in the business have the most positive impact. While the increase in wages for workers outside the family has a negative impact on the household economy.